The Effect of Apex Pruning on Vegetative and Generative Growth of Roselle (Hibiscus sabdariffa L.) - Slamet Susanto; Titistyas Gusti Aji; Arifah Rahayu (Jurnal Hortikultura Indonesia, 2013)
ABSTRACTThe  experiment  was  aimed  at  studying  the  effect  of  number  of  branch on  vegetative  and generative growth of roselle. The experiment was conducted at Cikabayan Experimental Farm from February  to June  2009. The  experiment was  arranged  in  randomized  complete  block  design with single factor and consisted  of four levels of pruning: control (without  pruning), apex pruning with 5 branches,  apex  pruning  with  10  branches,  and  apex  pruning  with 15  branches,  each  with  three replications.  The  result  indicated  that pruning  with  different  number  of  branch  gave  effect  on decreasing  on some  variables  of  vegetative  and  generative  growth  of  roselle.  Plants experienced apex pruning with 15 branches did not show any differences on number of primary stems, number of secondary  stems,  number  of  leaves, number  of  flowers,  fresh  and  dry  weight  of  calyxes,  and anthocyanin content  in  calyxes.  Plants  experienced  pruning  with  different  number  of branches tended to have higher  anthocyanin content  than  those  on  control. Generally, plants with 15 primary branches gave the best effect on both vegetative and generative growth of roselle.Keywords: Hibiscus sabdariffa L., pruning, branch, growth ABSTRAKPenelitian  ini  bertujuan  untuk  mempelajari  pengaruh  jumlah  cabang  pada pertumbuhan vegetatif dan generatif rosela. Penelitian dilaksanakan di  Kebun Percobaan Cikabayan pada bulan Februari sampai Juni 2009. Percobaan disusun dalam rancangan acak lengkap dengan faktor tunggal dan  terdiri  dari  empat tingkat  pemangkasan:  kontrol  (tanpa  pemangkasan),  pemangkasan pucuk dengan  5  cabang,  pemangkasan  pucuk   dengan  10  cabang,  dan pemangkasan  pucuk   dengan  15 cabang,  masing-masing  dengan  tiga ulangan.  Hasil  penelitian  menunjukkan  bahwa  pemangkasan dengan  nomor yang  berbeda  dari  cabang  memberi  efek  pada  penurunan  pada  beberapa variabel pertumbuhan vegetatif dan generatif rosela. Tanaman dengan pemangkasan pucuk pada 15 cabang tidak  menunjukkan  perbedaan  pada jumlah  batang  utama,  jumlah  sekunder  batang,  jumlah  daun, jumlah bunga,  berat  segar  dan  kering  calyxes,  dan  konten  antosianin  di  calyxes. Tanaman mengalami  pemangkasan  dengan  nomor  yang  berbeda  dari cabang  cenderung  memiliki  konten antosianin  lebih  tinggi  dibandingkan pada  kontrol.  Umumnya,  tanaman  dengan  15  cabang  utama memberikan efek terbaik pada kedua pertumbuhan vegetatif dan generatif rosela.Kata kunci: Hibiscus sabdariffa L., pemangkasan, cabang, pertumbuhan